The Category of Experience in Interpreting Oral History Recordings - Marcin Jarząbek (Wrocławski Rocznik Historii Mówionej, 2021)
The article indicates the importance of the category of experience in the interpretation of oral history recordings. Using the “stepwise” model of interpreting records, the article shows how the category of experience interacts with other possible levels of understanding of the story: language (narration), autobiographical memory, historical context and informational content.